Frames of the vaccination hesitant and impact on the propensity to vaccinate girls against the Human Papilloma Virus (HPV): A survey experiment study - Compagni, Amelia; Fattore, Giovanni; Paraggio, Diana (Mecosan - Management ed Economia Sanitaria - Open Access, 2026)
Vaccination hesitancy, i.e. the refusal or delay in being vaccinated, is a complex phenomenon influenced by numerous factors including the communicative messages to which individuals are exposed. Little is known about the impact that framing vaccination hesitancy as a problem and the vaccination hesitant as the responsible for such problem has on the propensity to vaccinate. In the study we report the results of a survey experiment in which respondents were randomly exposed to three different frames of the vaccination hesitant (as misinformed, anti-scientific and socially dangerous) and the impact of these frames on the intention to vaccinate girls against the human papilloma virus (HPV). The frames were derived from the press statements of the Italian Minister of Health between 2015 and 2017, and contained, besides different characterizations of the vaccination hesitant, the correspondent policy solutions to counteract such vaccination hesitancy. Findings show how framing the vaccination hesitant as anti-scientific or socially dangerous that, in turn, supports policies mandating vaccination and sanctioning the vaccination hesitant, tends to discourage vaccination. These findings alert us to the importance of designing with great care the communication about vaccinations and vaccination hesitancy and avoid counterproductive effects.